TRENDS IN THE DEVELOPMENT OF THE RESTAURANT SERVICES MARKET: METHODS OF DETERMINATION AND CHARACTERISTICS - Yudina, O. I.; Nebaba, N. O.; Korneyev, M. V.; Vyshnikina, O. V.; Altunin, K. O. (Systems and Technologies, 2024)
Methodical approaches to determining the current state and development trends of the restaurant services market which serve as a toolkit for forecasting future dynamic changes in the industry and planning measures for the adaptation of enterprises to the new conditions of the organization of their activities are considered in the article. The purpose of this article is the study of modern trends in the development of the restaurant services market and the formation of methodical approaches to their determination. In this study, based on the analysis of the external environment of restaurant establishments, the main methods for determining the current state of the catering services market are established, which include the methods of analyzing market stability, consumer preferences, competitive environment, and segmentation. With the help of the formed methodological toolkit, the following is carried out: survey of consumers; study of new popular dishes, recipes, technologies and trends in the industry; analysis of menus, concepts, price policy; forecasting future directions of industry development. The use of these methods allows: to determine the features of demand, supply and market equilibrium; evaluate and characterize changes in consumer needs; establish competitive advantages and disadvantages in the operation of the enterprise; determine the target audience according to established criteria. Based on the mentioned approaches and methods, the main trends affecting the development of the restaurant services market were identified and characterized. Thus, it was proven that the key directions of the development of the restaurant services market are the growing popularity of healthy food, the development of social media and information technologies, technological progress, and the development of gastronomic tourism. Certain methods are used as a tool for determining trends in the development of the industry, which provide the ability to adapt restaurant enterprises to dynamic changes in the service market. They include: marketing research methods, analysis of trends in the gastronomic industry, observation of competitors, cooperation with specialists and experts, analysis of changes in consumer demand. With the help of these methods, the main trends in the development of the restaurant business were determined, namely: economic, gastronomic, technological innovations, macroeconomic and demographic factors. These trends characterize the demand for restaurant services, the development of the restaurant business, digital development, changing consumption habits and the state of the consumer market.